2022
DOI: 10.1186/s13765-022-00753-3
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of low density polyethylene by Bacillus species

Abstract: Since its invention, polyethylene (PE) has brought many conveniences to human production and life. In recent years, however, environmental pollution and threats to human health caused by insufficient PE recycling have attracted widespread attention. Biodegradation is a potential solution for preventing PE pollution. In this study, Bacillus subtilis and Bacillus licheniformis, which are widespread in the environment, were examined for their PE degradation abilities. Biodegradation of low-density polyethylene (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…By adding TS, the bands appeared at regions of 3200–3400, 2850–2900, 1600–1700, 1300–1450, and 850–950 cm −1 are attributed to O‐H stretching and CH 2 stretching vibrations, ‐C‐C‐ stretching, O‐H bending, and ‐C‐C‐ bending, respectively. In addition, the bands at region of 960–1190 cm −1 correspond to a strong set of C‐O bending and stretching of the characteristic peaks for starch 23–26 . There was no change in LDPE peaks when it was blended with starch, indicating that PE and starch are immiscible.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…By adding TS, the bands appeared at regions of 3200–3400, 2850–2900, 1600–1700, 1300–1450, and 850–950 cm −1 are attributed to O‐H stretching and CH 2 stretching vibrations, ‐C‐C‐ stretching, O‐H bending, and ‐C‐C‐ bending, respectively. In addition, the bands at region of 960–1190 cm −1 correspond to a strong set of C‐O bending and stretching of the characteristic peaks for starch 23–26 . There was no change in LDPE peaks when it was blended with starch, indicating that PE and starch are immiscible.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, the bands at region of 960-1190 cm À1 correspond to a strong set of C-O bending and stretching of the characteristic peaks for starch. [23][24][25][26] There was no change in LDPE peaks when it was blended with starch, indicating that PE and starch are immiscible. The peak of 1721 cm À1 has appeared in the LD85/HD15/TS30 specimen, which may be related to the carbonyl group and possibly regarding to the oxidation reaction during the extrusion process.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
“…Our analysis revealed the presence of highly potentially active microorganisms engaged in carbon and nitrogen metabolism, suggesting a positive element cycle within the community. Methylobacterium , Geodermatophilus , Bacillus and Dietzia contribute to carbon availability through organic compound biodegradation (Kong et al, 2022 ; Sandhu et al, 2022 ; Venil et al, 2021 ; Yao et al, 2022 ; Yoshikawa et al, 2017 ; Zhang et al, 2013 ). Pseudomonas exhibited metabolic activity across all samples, suggesting active heterotrophic nitrification and aerobic denitrification processes over the dust particulates (Zhang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…This quality positions it as a promising microbial tool for biodegradation. Other than PET's degrading potential [68], Yao et al reported the ability of B. subtilis ATCC6051 to degrade PE [69], and it has been listed as a potential PU degrader [70].…”
Section: Sample 5: Soil Contaminated With Biopolymersmentioning
confidence: 99%